Film therapy : practical applications in a psychotherapeutic context - Fatemi, Mohsen Sayyed (New York, NY : Routledge, 2022)
"Unlike any book on the market, Film Therapy introduces a new paradigm in exploring the subtexts of movies and their potential therapeutic dimensions. The book illuminates how feature films can entail psychological components that can facilitate the therapeutic process. By elaborating the key concepts of each film and their psychological and psychotherapeutic discussions, it provides a demonstration of the films' practical applications in a therapeutic setting, opening a new world for understanding and exploring the dynamics of films in human interaction. The book powerfully delineates the rarely discussed role of films in psychological realms and argues how films can be educationally inspiring for therapists, psychologists, and educators"--
Keywords: Motion pictures in psychotherapy; Motion pictures -- Psychological aspects; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Psychotherapy / Couples & Family